Small Format Photography For Architectural Photogrammetry : A Review - Ahmad, Anuar (Fakulti Ukur dan Harta Tanah, 1994)
Today small format photography have been used widely in many applications of close range photogrammetry. This paper describes the use of small format photography in architectural photogrammetry. A few low cost systems developed for small format photography are also discussed.